Neuropsychological Consequences for Survivors of Childhood Brain Tumor in Malaysia - Alias, Hamidah; Lau, Sie Chong D.; Schuitema, Ilse; de Sonneville, Leo M. J. (Frontiers in Psychology, 2018)
Objective: This study aimed to evaluate neuropsychological consequences in survivors of childhood brain tumor. Method: A case-control study was conducted over a period of four months in a tertiary referral center in Kuala Lumpur, Malaysia. Fourteen survivors of childhood brain tumor aged 7 to 18 years, who were off-treatment for at least one year and were in remission, and 31 unrelated healthy controls were recruited. The median age at diagnosis was 8.20 years (range: 0.92 years to 12.96 years). The diagnoses of brain tumors were medulloblastoma, germ cell tumor, pineocytoma, pilocystic astrocytoma, suprasellar germinoma and ependymoma. Eleven survivors received central nervous system irradiation. Seven tasks were selected from the Amsterdam Neuropsychological Tasks program to evaluate alertness (processing speed), and major aspects of executive functioning, such as working memory capacity, inhibition, cognitive flexibility, and sustained attention. Speed, stability and accuracy of responses were the main outcome measures. Results: Survivors of childhood brain tumor showed statistically significant poorer performance on all tasks compared to healthy controls. Both processing speed and accuracy were impaired in the survivors, in particular under more complex task conditions. The survivors demonstrated deficits in alertness, sustained attention, working memory capacity, executive visuomotor control, and cognitive flexibility. Longer duration off treatment appeared to be correlated with poorer alertness, memory capacity, and inhibition. Conclusion: Survivors of childhood brain tumor in our center showed impaired neuropsychological functioning. Development of less toxic treatment protocols is important to prevent late effects of cognitive deficits in survivors of childhood brain tumor.